Towards effective screening for paternal perinatal mental illness: a meta-review of instruments and research gaps - Schöch, Philipp; Hölzle, Laura; Lampe, Astrid; Hörtnagl, Christine; Zechmeister-Koss, Ingrid; Buchheim, Anna; Paul, Jean Lillian (Frontiers in Public Health, 2024)
Background Paternal perinatal mental illness (PPMI), which affects around one in 10 fathers, is under-recognised despite increasing awareness of men’s mental health in the perinatal period. Social stigma and men’s reluctance to seek help exacerbate this gap. Neglecting the mental health needs of new fathers not only puts them at increased risk for mental illness themselves, but also has a profound and long-lasting impact on their families, children and their own self-esteem as they navigate their new role in the family dynamic. Objective This meta-review systematically identifies instruments assessing PPMI symptoms, evaluates their psychometric properties and applicability, presents key findings from studies using these tools, and identifies gaps and limitations in the literature on PPMI symptom assessment. Methods A systematic literature review was conducted using search strategies applied to PubMed, PsycNet APA, Cochrane, and Web of Science, supplemented by hand searches. Relevant information was extracted from each included study. Extracted data were analysed narratively to address the research questions. Results Findings identified limitations and gaps in current screening practices. While the Edinburgh Postnatal Depression Scale (EPDS) is the most widely used screening tool for both fathers and mothers, it inadequately captures atypical depressive symptoms in men. Cutoff scores lack consensus, and instrument sensitivity varies significantly due to cultural and sociodemographic factors. A number of other screening tools have been identified, most of which are more general and not specifically designed for perinatal mental health. Conclusion This meta-review broadens perspectives on PPMI screening instruments, highlighting key themes, patterns, and differences across the included reviews. While a variety of screening tools are used, the review underscores the necessity for tools specifically tailored to fathers during the perinatal period.